A feeding jejunostomy causing an intussusception – case report and literature review. Issue 9 (20th September 2022) - Tian, Jane; Bhatia, Shubham; Mourad, Youssef; Hall, Philip; Louis, Martine A; Khan, Noman
Abstract: Use of enteral nutrition has increased dramatically over the past two decades due to improved nutritional formulas, better quality feeding tubes and the ability to use less invasive endoscopic, fluoroscopic and laparoscopic techniques. Intussusception accounts for 1–5% of adult intestinal obstructions, with feeding tubes acting as a lead point in < 1% of cases. Since intussusception is rare, especially in adults, it is not always considered in the initial differential diagnosis of patients presenting with abdominal pain, nausea, vomiting or constipation. If left untreated, intussusception can eventually lead to bowel compromise, poor outcomes and even death. Therefore, prompt recognition and correction are necessary. We present a case of small bowel obstruction in an elderly male secondary to a tube-related intussusception. A review of the signs, symptoms and treatment recommendations is provided.